The prevalence of off-label use and supratherapeutic blood levels of outpatient psychotropic medication in suicidal adolescents - Hach, Isabel; Bertsch, Thomas; Nonell, Patrick (Frontiers in Psychiatry, 2024)
Introduction: Adolescents with mental disorders show an increased risk of suicidal phenomena. Vice versa suicidality is a serious adverse event of psychotropic drug therapy in adolescents. There are only few new psychotropic agents approved for this young age group. We evaluated the (prepandemic) prevalence of off-label use as well as detailed blood concentrations of outpatient psychotropic medication and sex differences in a clinical population of suicidal adolescents. Methods: The urine presence and serum levels of psychotropic substances of adolescents, hospitalized due to their acute suicidality, but without a known actual suicide attempt (i.e. no acute intoxication or serious self-injuries), were investigated routinely between 01.03.2017 and 31.01.2018. Urine (N=205) and blood samples (N=193) were taken at the beginning of closed inpatient admission, i.e. the results of the laboratory analysis reflect outpatient drug intake. The serum levels of psychopharmacological medication and OTC-medication were measured. Results: Our sample consists of 231 cases (males: N=54; females: N=177, ratio: 1:3,3), aged 12-17 years (average age: 15,4 years). The most prevalent psychiatric diagnoses were depressive episodes (54%) and adjustment disorders (25%), females were more often diagnosed with depressive disorders than males (male/female ratio: 1:9.5, p<0.0001). More than half of adolescents (56%) used at least one prescribed psychotropic drug at admission (24.8% > two psychotropic drugs). Off-label use of second generation antipsychotics was significantly more frequent than off-label use of antidepressants (85% vs. 31%, p< 0.01). Adolescents suffering from depressive disorders were significantly more often onlabel treated than adolescents with neurotic or stress-related disorders (56% vs. 10%). Female cases with prescribed psychotropic drug use showed significantly more frequent supratherapeutic drug levels than male cases (5% vs. 27%, p< 0.05). Conclusion: Female adolescents may have an increased risk of supratherapeutic blood levels, especially when outpatient prescribed psychotropic drugs are off-label used. Measurement of blood levels of outpatient prescribed psychotropic drugs could be used to enhance the safety and efficacy of the individual psychopharmacological treatment of adolescent suicidal patients. There is an urgent need for more real-world evidence on the effective treatment of adolescents with psychotropic drugs.